2015
DOI: 10.1111/jcmm.12439
|View full text |Cite
|
Sign up to set email alerts
|

Immuno‐modification of enhancing stem cells targeting for myocardial repair

Abstract: Despite the controversy in mechanism, rodent and clinical studies have demonstrated beneficial effects of stem/progenitor cell therapy after myocardial infarction (MI). In a rat ischaemic reperfusion MI model, we investigated the effects of immunomodification of CD 34+ cells on heart function and myocardial conduction. Bispecific antibody (BiAb), consisting of an anti-myosin light chain antibody and anti-CD45 antibody, injected intravenously was used to direct human CD34+ cells to injured myocardium. Results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The conjugation of SLeX on the MSC surface is stable, versatile, and induces a robust rolling response on P‐selectin coated substrates . It was also reported that the conjugation of stem cells with bispecific antibodies can be directly injected and retained by injured myocardium or targeted to injured myocardial tissues for tissue regeneration . These methods offer a simple approach to explore engineered cell homing and potentially target any cell type to specific tissues via the circulation.…”
Section: Goals Of Cell Engineeringmentioning
confidence: 99%
“…The conjugation of SLeX on the MSC surface is stable, versatile, and induces a robust rolling response on P‐selectin coated substrates . It was also reported that the conjugation of stem cells with bispecific antibodies can be directly injected and retained by injured myocardium or targeted to injured myocardial tissues for tissue regeneration . These methods offer a simple approach to explore engineered cell homing and potentially target any cell type to specific tissues via the circulation.…”
Section: Goals Of Cell Engineeringmentioning
confidence: 99%
“…Nonetheless, systemic administration via IVI is not ideal because there is always a high degree of cell distribution to outer tissues [35,54]. We consider more useful to maximize the delivery of stem cells to heart by, for instance, making use of bispecific antibodies in addition to IVI, such as the one reported by Yu et al [118], than to resort to invasive approaches. The idea behind the use of bispecific antibodies is to direct stem cells injected intravenously directly to the myocardium due to the dual antibody-based recognition of stem cell's cluster of differentiation and of myosin light chains, exposed in injured cardiomyocytes.…”
Section: Clinical Translationmentioning
confidence: 99%